Single strand DNA breaks in mitogen stimulated T lymphocytes are religated by a mechanism independent of accessory cells. - Harrison, D J (1989)
The phenomenon of religation of single-strand DNA breaks (nicks) in mitogenically stimulated human T lymphocytes is an event occurring within 8 h of mitogen stimulation. Many later events in lymphocyte activation are known to be dependent on accessory cells, whereas earlier events are often accessory-cell independent. To establish whether nick religation is dependent or independent of accessory-cell function, lymphocytes were stimulated with PHA in the presence of inhibitors thought to act, in part at least, on accessory cells (methylprednisolone and cyclosporine A), or under conditions in which accessory-cell function is limited (low-density culture, adherent-cell depleted populations). In each case DNA synthesis was inhibited but the religation process was retained, indicating that it is independent of accessory-cell function. Inhibition of DNA synthesis in these cells was shown to be readily reversible on addition of conditioned medium containing accessory-cell products, but there was no further change in ligation.